HISTORY OF WORLD COUNCIL OF CHURCHES IN AMSTERDAM - Paath, Jeane; David Baluseda; Harefa, Febriaman Lalaziduhu; Kaseke, Fanny Yapi Markus (Jurnal Matetes STT Ebenhaezer, 2023)
The World Council of Churches is an official organization formed for the benefit of the church to promote the unity and unity of the churches in the world. This organization belongs to the ecumenical movement that directs the church to participate in paying attention to the conditions that occurred after the world war, especially at the formation of the World Council of Churches in Amsterdam in 1948. The form of participation of the World Council of Churches can be seen from social actions and efforts in carrying out reforms both spiritually and in circumstances. national church related. According to the author, students need to understand the background of the formation of this movement comprehensively in order to add insight from the history of the formation of ecumenical organizations in the world, therefore, the author will describe the history of the formation of the World Council of Churches through descriptive methods and literature review by collecting various kinds of data related to the subject to be reviewed